Efficacy and Safety of Hydrogen Therapy in Patients with Early-Stage Interstitial Lung Disease: A Single-Center, Randomized, Parallel-Group Controlled Trial - Tang C; Wang L; Chen Z; Yang J; Gao H; Guan C; Gu Q; He S; Yang F; Chen S; Ma L; Zhang Z; et al. (Dove Medical Press, 2023)
Chang Tang,1,2,* Lanting Wang,1,2,* Zihua Chen,1,2,* Jin Yang,1,2 Haiqing Gao,1,2 Chenggong Guan,1,2 Qiaozhi Gu,1,2 Shan He,1,2 Fanping Yang,1,2 Shengan Chen,1,2 Li Ma,1,2 Zhen Zhang,1,2 Ying Zhao,1,2 Lin Tang,1,2 Yu Xu,1,2 Yue Hu,3 Xiaoqun Luo1,2 1Department of Allergy & Immunology, Huashan Hospital Affiliated to Fudan University, Shanghai, People's Republic of China; 2Department of Dermatology, Huashan Hospital Affiliated to Fudan University, Shanghai, People's Republic of China; 3Department of Clinical Laboratory, Huashan Hospital Affiliated to Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoqun Luo, 12 Wulumuqi Zhong Road, Jing'an District, Shanghai, People's Republic of China, Tel +86 13918825230, Email luoxiaoqun913@126.comPurpose: Several in vivo experiments have shown that molecular hydrogen is a promising therapeutic agent for interstitial lung diseases (ILD). In this study, hydrogen therapy was investigated to determine whether it is superior to N-Acetylcysteine (NAC) for the treatment of patients with early-stage ILD.Patients and Methods: A prospective, single-center, randomized, controlled clinical trial was conducted in 87 patients with early-stage ILD. Hydrogen or NAC therapy was randomly assigned (1:1 ratio) to the eligible patients. The primary endpoint was the change in the high-resolution computed tomography (HRCT) and composite physiologic index (CPI) scores from baseline to week 48. Pulmonary function was evaluated as a secondary endpoint, and adverse events were recorded for safety analysis.Results: The rate of HRCT image improvement from the baseline in the HW group (63.6%) was higher than that in the NAC group (39.5%). A significant decrease in CPI and improvement in DLCO-sb were observed in the hydrogen group compared with those in the control group. Changes in other pulmonary function parameters, including FVC, FEV1, FEV1/FVC%, and TLC, were not significantly different between the two groups. Adverse events were reported in 7 (15.9%) patients in the HW group and 10 (23.3%) patients in the NAC group, but the difference was not significant (P=0.706).Conclusion: Hydrogen therapy exhibits superior efficacy and acceptable safety compared with NAC therapy in patients with early-stage ILD.Keywords: hydrogen, N-acetylcysteine, interstitial lung disease, therapeutic effects